COMPARATIVE ANALYSIS OF THE TRIPS AGREEMENT AND UZBEKISTAN'S LEGISLATION ON INTELLECTUAL PROPERTY RIGHTS - Rakhmonova Mokhichekhra Nodirbek qizi (Scholar Express Journals, 2024)
This article explores the alignment between the TRIPS Agreement and the intellectual property (IP) legislation of Uzbekistan. Through a detailed comparative analysis, it examines the legal framework governing IP in Uzbekistan and evaluates its compliance with international standards. The study highlights key areas of divergence and provides recommendations for further harmonization. This research contributes to the understanding of the challenges faced by Uzbekistan in integrating global IP norms into its national legal system
Keywords: TRIPS Agreement; Intellectual Property; Uzbekistan Legislation